Behavior and design of axially loaded high-strength concrete-filled circular aluminum tubular short columns. (October 2022) - Yan, Xi-Feng; Ahmed, Mizan; He, Meng-Nan
Abstract: Concrete-filled aluminum tubular (CFAT) columns inherit superior mechanical performance in terms of strength and ductility and offer excellent corrosion resistance. However, due to the limited investigation, the performance of CFAT columns has not been fully understood yet. This paper presents a new fiber element (FBE) model for nonlinear analysis of axially loaded high-strength CFAT short columns with circular sections. The accurate constitutive material models of aluminum and confined concrete utilized in the FBE model are presented. On the basis of test results, a novel lateral confinement model is developed to determine the confinement effect of outer aluminum tubes on core concrete in circular CFAT columns. A new strength degradation factor for quantitatively determining the post-peak behavior of the confined concrete in CFAT circular columns is also proposed and incorporated into the FBE model. The proposed FBE model is validated through comparisons with test results compiled from published literature, predictions by three-dimensional finite element (3D FE) modeling and the existing lateral pressure model of CFAT columns proposed by another researcher. Parametric studies are implemented to ascertain the influences of key variables on the performance of the CFAT columns. The experimental and numerical data are utilized to examine the applicability of current design standards for the design of conventional concrete-filled steel tubular (CFST) columns in designing CFAT columns. A new strength design formula is proposed to predict the compressive ultimate strengths of CFAT columns and validated by comparing with test results and the ones obtained from FBE analyses. Overall, it is found that the proposed FBE model and design formula can predict well the axial responses of high-strength CFAT short columns with circular cross-sections.